Determination of sources of aerosol in Chicago by chemical element mass balance - Mohd. Yusoff, Mohd. Rashid; Scheff, Peter Allan (1987)
A chemical element mass balance (CEB) receptor model was used to determine the contributions from cool combustion cement and limestone, mobile sources, refuse incineration, soil and steel industries to the ambient particulate matter in Chicago.